Studying Sex Effect on CTGF, TGF-B1 Levels and Some Relevant Parameters in Iraqi Diabetic Patients with Glomeruli and Renal Tubules Fibrosis: - khuldon Ibrahim, Reham; K. Ghudhaib, Kadhim; Dyab Allawi, Ali Abdulmajid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Due to high blood sugar over long periods, the incidence and prevalence of type 2 diabetes are increasing throughout the world. Diabetic complications include microvascular and macrovascular complications that target the kidneys, nerves, eyes, and heart. Hence, the current study aimed to investigate the levels of (CTGF) and (TGF-β1) for both men and women and to demonstrate the effect of sex on it. In addition, some related biochemical factors in patients with diabetes and diabetic nephropathy are compared with those in healthy controls. The study included 120 males and females with an age range of (30-65) years old. Ninety patients with type 2 diabetes were subdivided into three groups on the basis of ACR criteria. All the individuals in the groups visited Baghdad Teaching Hospital, Medical City, and Al-Yarmouk Teaching Hospital during the period between December 2021 and May 2022. The CTGF and TFG-β1 levels were determined using the ELISA technique. Urea results showed statistically significant differences between diabetic nephropathy in the patient group and the control group in female cases. Still, there were no statistically significant differences between male patients with diabetic nephropathy and the control group. The results also revealed that there were statistically significant differences in ACR, eGFR, urea, FBS, and creatinine between the diabetic nephropathy group and the healthy group for both men and women. From our results, CTGF and TGF-β1 represent good early prognostic markers in diabetic nephropathy.